Human rights perspectives on climate change adaptation: Civil society experiences in Cambodia and Kenya - Christoplos, I.; Funder, M.; McGinn C; Wairimu W (Danish Institute for International Studies, 2014)
A growing number of civil society organisations apply human rights based approaches in their work. But what are the practical experiences with such approaches in climate change adaptation?